Placebo and nocebo effects in youth: subjective thermal discomfort can be modulated by a conditioning paradigm utilizing mental states of low and high self-efficacy. Issue 1 (February 2022) - Weik, Ella; Neuenschwander, Regula; Jensen, Karin; Oberlander, Tim F; Tipper, Christine
Introduction: Conditioning is a key mechanism of placebo and nocebo effects in adults, but little is known about these effects in youth. This study investigated whether personalized verbal cues evoking a sense of high or low self-efficacy can induce conditioned placebo and nocebo effects on subjective discomfort of noxious heat in youth. Methods: In a structured interview, 26 adolescents (13–18 years) described personal situations in which they experienced a sense of high, low or neutral self-efficacy. Participants were then asked to recall these memories during a conditioning paradigm, in which a high thermal stimulus applied to the forearm was repeatedly paired with a low self-efficacy cue and a low thermal stimulus with a high self-efficacy cue. In a testing phase, high, low and neutral self-efficacy cues were paired with the same moderate temperature. We hypothesized that conditioned high and low self-efficacy cues would induce conditioned placebo and nocebo responses to moderate temperatures. Results: Moderate temperatures were rated as more uncomfortable when paired with the conditioned low compared with the neutral self-efficacy cue (nocebo effect). While in the whole-group analysis, there was no significant difference between ratings of moderate thermal stimuli paired with high compared with neutral self-efficacy cues (placebo effect), a sub-group of participants with a greater range of emotional valence between high and neutral self-efficacy cues revealed a significant placebo effect. The strength of the nocebo effect was associated with higher anxiety and lower hope. Conclusion: Conditioned associations using internal self-efficacy states can change subjective discomfort of thermal sensations.